Overconfidence and team-performance: An analysis of NBA-players' self-perception - Hannah Geyer; Hanke Wickhorst (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2011)
We analyse the effect of overconfidence in a model of team-production with effort complementarities. We show that overconfidence may not only enhance an overconfident agent's effort but also that of a rational one. Focusing the agents' payoffs we see that this increase in effort can be to the agents' benefit, regardless whether they are rational or overconfident. We take this notion to NBA-data which we have gained from the season 2009/10 and see that players who have been identified as overconfident have a significantly positive effect on their team's success. – – Wir betrachten den Effekt von Overconfidence mit Hilfe eines intuitiven Modells einer Team-Produktion mit komplementären Arbeitseinsätzen. Es zeigt sich, dass Overconfidence nicht nur den Arbeitseinsatz des betroffenen Agenten erhöht, sondern gleichzeitig den eines rationalen Teammitglieds. Hieraus resultiert ein Nutzenvorteil für die Agenten, unabhängig davon, ob sie selbst rational oder overconfident sind. Daten der NBA-Saison von 2009/10 zeigen, dass Spieler, welche als overconfident identifiziert wurden, einen signifikant positiven Effekt auf den Erfolg ihres Teams haben.
Keywords: D21; D62; L23; 650